Vitreous concentrations of vascular endothelial growth factor as a potential biomarker for postoperative complications following pars plana vitrectomy - Faruk Nisic (Termedia Publishing House, 2019)
Introduction The aim of the study was to investigate the effects of vascular endothelial growth factor (VEGF) concentration in vitreous on postoperative complications after pars plana vitrectomy (PPV).